A decision support system based on simulation for airline boarding problem - ALABAŞ USLU, ÇİĞDEM (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2019)
Travelling by airplanes is an increasingly popular and preferred way of transportation. Due to the increasing demand, airplane companies aim to have highest profit and the best service to their passengers. Since airplanes make money just when they are on the air, flight frequency has to be increased. Preparation of the aircraft and taking passengers into aircraft is knows as passenger boarding which is one the crucial factor to decrease turn-over time. The most appropriate way to prepare aircraft and taking passengers into aircraft within possible minimum time may yield enormous profit for airplane companies. Decrement in the duration of boarding process also has a positive impact on passenger satisfaction. In this study, a Decision Support System (DSS) has been developed to help generation and evaluation new boarding methods. DSS calculates mean interferences for new boarding methods created by user and compares these methods in terms of the number of interferences. Also, in this study two different boarding methods have been suggested and tested by using developed DSS. Tests showed that either suggested methods have less mean interferences than the other methods which are available in the literature or they are simpler and more realistic to apply into real-life.
Keywords: Airplane boarding problem; Passenger interferences; decision support system